PENGEMBANGAN LKPD MATERI PECAHAN DESIMAL BERBASIS PENDEKATAN TEACHING At THE RIGHT LEVEL (TARL) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MATEMATIKA KELAS IV SEKOLAH DASAR - Nur Kasella, Dinda; Susanta, Agus; Parmadi, Bambang (Jurnal Kajian Pendidikan Dasar, 2025)
This research aims to develop TaRL-based student worksheets to improve students' cognitive learning outcomes in grade IV decimal fraction material in elementary schools. The type of research used in this research is development research. The research subjects were fourth grade students at SD Negeri 10 South Bengkulu as the experimental class and control class. Data collection techniques use needs questionnaires, response questionnaires and tests. Research instruments use needs analysis instruments, expert validation instruments, product trial instruments, product effectiveness test instruments. Data analysis in this research was carried out by analyzing expert validity data, rater/researcher agreement, standardization of instruments, description of learning outcome profiles. Based on the research results, it can be concluded that the development of Teaching at The Right Level (TaRL) based student worksheets to improve students' cognitive learning outcomes which were developed according to material expert validators, language validators and media validators was declared suitable for use in the learning process. From the posttest results of class IV students at SD Negeri 10 South Bengkulu, it is known that the use of TaRL-based student worksheets has had a positive impact on students in terms of improving students' cognitive learning outcomes.